1978
DOI: 10.1103/physrevc.17.1368
|View full text |Cite
|
Sign up to set email alerts
|

Energy spectra of nuclear fragments produced by high energy protons

Abstract: Fragment energy spectra from the 2.1-and 4.9-GeV proton irradiation of C, Al, Ag, and U targets were measured at several angles to the beam for products ranging from He up to Ar for the heavier targets. The fragments were detected in a telescope consisting of a gas AE counter and a silicon E counter. The carbon target measurements are compared with previous data from projectile fragmentation studies. A Maxwellian type functional form which fits the energy spectra from all the targets is presented. The spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(63 citation statements)
references
References 36 publications
4
59
0
Order By: Relevance
“…Multifragmentation was seen in high-energy proton-nucleus collisions [15][16][17][18] before systematic studies were undertaken in nucleus-nucleus collisions. For a proton incident on a nucleus the picture is as follows.…”
Section: Experimental Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Multifragmentation was seen in high-energy proton-nucleus collisions [15][16][17][18] before systematic studies were undertaken in nucleus-nucleus collisions. For a proton incident on a nucleus the picture is as follows.…”
Section: Experimental Overviewmentioning
confidence: 99%
“…Most early multifragmentation experiments are inclusive measurements [15][16][17][18][19][20], i.e. particles are identified with no requirements that other particles from the same event should be detected in coincidence.…”
Section: Event Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…For lighter projectiles (from p to 20 Ne) with energies above 1 -10 Gev/nucl, studies have observed structureless, exponentially decaying inclusive and non-inclusive energy spectra, often accompanied by slight oscillations over the range of projectiles and projectile energies, targets, and registered final fragments (see, for example, [1][2][3][4][5][6][7][8]). For heavier projectiles these phenomena were observed even for smaller energies (see, for instance, [9]).…”
Section: Introductionmentioning
confidence: 99%